Light Novel Puti Legenda Siamang Putih (International Forum of Researchers and Lecturers, 2023)
Light novel are a form of lightweight novels that originate from Japan and are usually aimed at teenage readers. Light novels have various characteristics, including the user of informal language, and lighter and easier-to-read stories. This design aims to present areading material that can be accepted by the younger generation with the Minangkabau cultural influence in the frorm of the Sumbang Duo Baleh Gadih Minang. Data was collected through observation, literature research, and questionnaires, and then analyzed using the 5W+1H method. This design will result a light novel book titled “Puti: the legend of the whit gibbon”, which will present a fantasy story blended with Minangkabau culture. Supported by media such as w-banners, web banners, web novels, bookmarks, posters, totebags, and notebooks.